Recent Advances in Diagnosis and Treatment of Vestibular Disorders - Perez-Fernandez, Nicolas; Ramos-Macias, Angel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Vestibular medicine relates to the assessment, diagnosis, and treatment of patients with dizziness and vertigo. In all these fields, there has been an enormous increase in research during recent years. This edition includes a discussion on the epidemiology of dizziness, the role of genetics in the development of vestibulopathy, diagnostic approaches, and interventions for patients with dizziness and vertigo: medical treatment, surgery, and vestibular rehabilitation.